Evaporation over India (MAUSAM, 1971)
Evaporation observations recorded with wire-mesh covered Class A pans at about 80 stations in India for, a period of five years or more have been used to present monthly and annual evaporations maps. Highest evaporation values of 16-17 mm per day are recorded in north Maharashtra, southwest Madhya Pradesh and Rajasthan in May, while dally evaporation is lowest (